Transparent on-demand co-allocation data access for grids. (7th May 2010) - Chen, Po-Cheng; Chang, Jyh-Biau; Lin, Yi-Sheng; Shieh, Ce-Kuen; , Yi-Chang Zhuang
This paper presents a data sharing system called On-Demand data Co-Allocation (ODCA). ODCA integrates the advantages of the co-allocation concepts with the conventional on-demand data access scheme. It transfers the necessary file fragments from multiple data sources only when the application demands, thereby reducing data transmission time, wasted network bandwidth and required storage space. Moreover, it facilitates legacy applications to transparently access distributed grid data by using the native I/O system calls. The experimental results indicate that ODCA achieves superior performance in the turnaround time of data-intensive applications than the pre-staging and the on-demand access schemes.